Electromagnetic shielding effectiveness and functions of stainless steel/bamboo charcoal conductive fabrics. (November 2014) - Hwang, Po-Wen; Chen, An-Pang; Lou, Ching-Wen; Lin, Jia-Horng
Following technological advancements, there is a growing population of cellular phone and computer users. However, these electronic instruments cause electromagnetic waves, negatively influencing users' health or precision instruments' malfunction. Therefore, shielding electromagnetic wave becomes an important matter. In this study, stainless steel wires and bamboo charcoal roving are made into conductive yarn with 6 turns/cm by ring spinning machine. On a 14-gauge automatic horizontal knitting machine, the resulting yarn is then knitted into stainless steel/bamboo charcoal conductive fabrics and then evaluated for the electrical property and functions. According to experimental testing, electromagnetic shielding effectiveness (EMSE) of the fabrics increases with an increase in stainless steel content and number of lamination layers. In particular, when laminated at an angle of 0°/45°/90°/−45°/0°/45°, the fabrics have an EMSE of above 30 dB at an incident frequency between 2010 and 2445 MHz. The far infrared emissivity increases with bamboo charcoal content, reaching the maximum of 0.9 ɛ, when the fabric was made by one-cycle polyethylene terephthalate (PET)/stainless steel/bamboo charcoal plied yarn in the first feeder and four-cycle PET/bamboo charcoal plied yarn in the second feeder.